A TALE of Transposition: Tn3-Like Transposons Play a Major Role in the Spread of Pathogenicity Determinants of Xanthomonas citri and Other Xanthomonads - Rafael Marini Ferreira (American Society for Microbiology, 2015)
ABSTRACT Members of the genus Xanthomonas are among the most important phytopathogens. A key feature of Xanthomonas pathogenesis is the translocation of type III secretion system (T3SS) effector proteins (T3SEs) into the plant target cells via a T3SS. Several T3SEs and a murein lytic transglycosylase gene (mlt, required for citrus canker symptoms) are found associated with three transposition-related genes in Xanthomonas citri plasmid pXAC64. These are flanked by short inverted repeats (IRs). The region was identified as a transposon, TnXax1, with typical Tn3 family features, including a transposase and two recombination genes. Two 14-bp palindromic sequences within a 193-bp potential resolution site occur between the recombination genes. Additional derivatives carrying different T3SEs and other passenger genes occur in different Xanthomonas species. The T3SEs include transcription activator-like effectors (TALEs). Certain TALEs are flanked by the same IRs as found in TnXax1 to form mobile insertion cassettes (MICs), suggesting that they may be transmitted horizontally. A significant number of MICs carrying other passenger genes (including a number of TALE genes) were also identified, flanked by the same TnXax1 IRs and delimited by 5-bp target site duplications. We conclude that a large fraction of T3SEs, including individual TALEs and potential pathogenicity determinants, have spread by transposition and that TnXax1, which exhibits all of the essential characteristics of a functional transposon, may be involved in driving MIC transposition. We also propose that TALE genes may diversify by fork slippage during the replicative Tn3 family transposition. These mechanisms may play a crucial role in the emergence of Xanthomonas pathogenicity. IMPORTANCE Xanthomonas genomes carry many insertion sequences (IS) and transposons, which play an important role in their evolution and architecture. This study reveals a key relationship between transposons and pathogenicity determinants in Xanthomonas. We propose that several transposition events mediated by a Tn3-like element carrying different sets of passenger genes, such as different type III secretion system effectors (including transcription activation-like effectors [TALEs]), were determinant in the evolution and emergence of Xanthomonas pathogenicity. TALE genes are DNA-binding effectors that modulate plant transcription. We also present a model for generating TALE gene diversity based on fork slippage associated with the replicative transposition mechanism of Tn3-like transposons. This may provide a mechanism for niche adaptation, specialization, host-switching, and other lifestyle changes. These results will also certainly lead to novel insights into the evolution and emergence of the various diseases caused by different Xanthomonas species and pathovars.